Peer Mentoring in the Do-it-Yourself Artificial Pancreas System Community. (November 2020) - Crocket, Hamish
Background: The do-it-yourself (DIY) artificial pancreas system (APS) community is led by people with diabetes (PWD) and their families. In contrast to standard models of care, in which health care professionals are responsible for the education and training of PWD and their families, within the DIY APS, community users are reliant on their peers for education and training. The provision of this support has not previously been studied. This article focuses on the role of mentors within the DIY APS community. Method: Semistructured interviews were conducted with mentors ( n = 9) who were identified with assistance from the DIY APS community. Thematic analysis was undertaken. Results were presented to select participants who endorsed the results as an accurate description of mentoring in the DIY APS community. Results: Mentors' primary motivation was altruism. An empathetic, process-focused approach was modeled by prominent mentors. The use of online forums as the primary source of user support was perceived to be an effective method for sharing the workload. Key challenges for mentors included the frequency with which users asked questions that were answered in the existing documentation, dealing with conflict and managing workload. Most participants did not perceive mentoring to be risky, but did take steps to ensure that users were taking responsibility for their own systems. Conclusion: This study is the first to examine the role of mentors within the DIY APS community and also within the broader diabetes online community. Future research might seek to quantify the empathetic, process-focused approach to mentoring.